2012
DOI: 10.1080/15248372.2012.691143
|View full text |Cite
|
Sign up to set email alerts
|

Using EEG to Study Cognitive Development: Issues and Practices

Abstract: Developmental research is enhanced by use of multiple methodologies for examining psychological processes. The electroencephalogram (EEG) is an efficient and relatively inexpensive method for the study of developmental changes in brain-behavior relations. In this review, we highlight some of the challenges for using EEG in cognitive development research. We also list best practices for incorporating this methodology into the study of early cognitive processes. Consideration of these issues is critical for maki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
155
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 196 publications
(160 citation statements)
references
References 36 publications
(43 reference statements)
3
155
0
2
Order By: Relevance
“…To this end, we separate this section into four different aspects of the mu methodology: (1) considerations regarding baseline; (2) considerations for action observation and execution trials; (3) considerations regarding stimulus duration, outliers, and minimal amount of usable data; and (4) considerations regarding frequency bands, reference type, and scalp distribution. Although some of these topics have been addressed in behavioral or other developmental EEG papers (for reviews, see Bell & Cuevas, 2012; Fox, Schmidt, Henderson, & Marshall, 2007), our review of the infant mu literature revealed that these topics were the most salient to infant mu researchers for enhancing between study comparisons.…”
Section: Methodological Considerations Of Infant Eeg Mu Rhythm Researmentioning
confidence: 94%
“…To this end, we separate this section into four different aspects of the mu methodology: (1) considerations regarding baseline; (2) considerations for action observation and execution trials; (3) considerations regarding stimulus duration, outliers, and minimal amount of usable data; and (4) considerations regarding frequency bands, reference type, and scalp distribution. Although some of these topics have been addressed in behavioral or other developmental EEG papers (for reviews, see Bell & Cuevas, 2012; Fox, Schmidt, Henderson, & Marshall, 2007), our review of the infant mu literature revealed that these topics were the most salient to infant mu researchers for enhancing between study comparisons.…”
Section: Methodological Considerations Of Infant Eeg Mu Rhythm Researmentioning
confidence: 94%
“…Although EEG has excellent temporal resolution, it has relatively poor spatial resolution (Bell & Cuevas, 2012). Thus, the specific neuronal populations or subcortical structures that contribute towards electrical activity at any particular site cannot be reliably inferred (Bell & Cuevas, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, EEG power has a long tradition as a measure of brain development (see Bell, 1998; Bell & Fox, 1994, for reviews). The EEG signal reflects post-synaptic activity and EEG power (level of mean square microvolts of the EEG signal resulting from Fourier analysis) reflects the excitability of groups of neurons (Bell & Cuevas, 2012). With respect to brain development during infancy, more neural activity translates into higher EEG power.…”
mentioning
confidence: 99%